Sources of Information for Social Studies Teachers and their Level of usage in Abeokuta, Ogun State Nigeria - Amos, Adediran Adekunle (Information Management and Business Review, 2012)
The study examined sources of information for teachers in social studies and their level of usage in secondary schools. The design of this study was descriptive of survey type. Data was collected from twentyfour (24) secondary schools and was randomly selected from Abeokuta north local government and Abeokuta south local government area of Ogun state, Nigeria. Ninety-seven (97) secondary schools female and male teachers of different age- grades, qualifications and experience were used as sample. Questionnaire was made use of for data collection. The questionnaire was the close-ended likert- type technique that expresses degree of agreement or disagreement with he supplied statement. Data was analyzed using standard deviation, students- t-test statistics, mean and rank order. The findings of the study revealed that, teachers’ sources of information for social studies include reference materials, newspapers, journals, literary materials, historical monuments and artefacts, television, textbooks, resource person, magazines, pamphlet, bulletins and radio. Computer component, such as e-mail, file transfer protocol, World Wide Web (www) rarely used by social studies teachers. Recommendations were made which includes computer training be provided for social studies teachers at all level of education in Nigeria and modern information centers with integrated circuits and digital communication to link schools should be provided at local levels for the use of teachers, particularly for social studies teachers.